Analisis Interseksional Gender, Etnis, dan Kelas Sosial: Pembacaan Poskolonial Terhadap The Handmaiden (2016) - Madinatul Munawarah (School of Communication Science and Media Business, 2023)
The Handmaiden is one of the South Korea’s films that gain international success, not only because of global distribution, but also because the film shows explicit lesbian scene. Park Chan Wook, the director, uses The Handmaiden as critique of homophobia in South Korea. He borrows narration of gender and sexuality from The Fingersmith, a British novel by Sarah Water, but he draws it into the narration of ethnicity or colonialism by changing the film’s setting. This changing could be categorized as a mockery, as in Bhabha’s concept, for resistance of South Korea’s compliance to the west. This research brought three perspectives: feminism, colonialism, and intersectionality, and by using deconstructive method to dismantle the binary of every entity: gender, class, and ethnicity. The research indicate that ethnicity superiority was broken by social class, and male superiority was defeated too by women with high social class. In The Handmaiden, the social class, especially economy, looks more dominant than gender and ethnicity. Keywords: intersectionality, gender, colonialism, feminism, power structure